Orchards, Santa Cruz Valley, Trinidad, B.W.I. - (:unkn) unknown (Picture-Point Publications, New York, 2010)
A picture from a hilltop overlooking the Santa Cruz Valley with the Northern Range deep blue and towering in the background. Postcard number 38836.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mountains--Trinidad and Tobago; Forests and forestry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Santa Cruz; Valleys--Trinidad and Tobago; Orchards--Trinidad and Tobago; Fruit trees--Trinidad and Tobago; Tropical fruit--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; [1960]